The Effect of Instructional Media Use on Elementary Students’ Learning Interest and Learning Outcomes - Catur Cahya Ningrum; Abu Dharin (Indonesian Journal of Innovative Teaching and Learning, 2026)
Background: This study is grounded in the limited use of instructional media in classroom instruction, which contributes to low student interest in learning, reduced motivation, and suboptimal academic outcomes at the elementary school level. Objective: The purpose of this research is to examine the effect of instructional media use on students’ learning interest and learning outcomes at SD Negeri Kaliputih. Method: This study employed a quantitative field research design using a survey method. The population consisted of 174 students, with a sample of 63 students from grades 1 to 6 selected for analysis. Data were collected through questionnaires and documentation and analysed using multiple linear regression, preceded by prerequisite tests including normality, linearity, and F-tests. Result: The findings indicate a statistically significant effect of instructional media and learning interest on student learning outcomes, with a combined contribution of 41.9%. In comparison, the remaining 58.1% is influenced by other factors not examined in this study. Conclusion: The effective use of instructional media plays a vital role in enhancing student engagement and academic achievement. Contribution: This research contributes empirical evidence supporting the integration of instructional media as a strategic approach to improve elementary learning processes and outcomes.